Strategi Pengembangan Produk Olahan Daun Kelor Sebagai Superfood Lokal: Studi Kasus Pada UMKM Kampoeng Kelor Di Boyolali - Mustaqim Iswanto; Yuni Prihadi Utomo (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze product development strategies for processed moringa leaves as a local superfood through a case study of the Kampoeng Kelor MSME in Boyolali Regency, Indonesia. Kampoeng Kelor is a community-based enterprise that integrates moringa-based production, education, and tourism within a single agro-edutourism ecosystem. Employing a Participatory Research approach, the researcher was directly involved in the enterprise's activities during the 2024 Wirausaha Merdeka program. Data were collected through observation, interviews, and active participation, and analyzed using qualitative descriptive methods and SWOT analysis. The findings indicate that Kampoeng Kelor holds significant potential in developing functional food products from moringa, yet faces internal constraints such as limited raw materials and production tools, as well as external challenges like low market literacy. Recommended strategies include strengthening production capacity, increasing public education on moringa's health benefits, improving business management, and expanding partnership networks. This study underscores the importance of collaborative and contextual approaches in developing local commodity-based MSME to enhance their sustainable competitiveness in both domestic and global markets.